A retrovirus-based protein complementation assay screen reveals functional AKT1-binding partners - Ding, Zhiyong (National Academy of Sciences, 2006)
We developed a retrovirus-based protein-fragment complementation assay (RePCA) screen to identify protein–protein interactions in mammalian cells. In RePCA, bait protein is fused to one fragment of a rationally dissected fluorescent protein, such as GFP, intensely fluorescent protein, or red fluorescent protein. The second, complementary fragment of the fluorescent protein is fused to an endogenous protein by in-frame exon traps in the enhanced retroviral mutagen vector. An interaction between bait and host protein (prey) places the two parts of the fluorescent molecule in proximity, resulting in reconstitution of fluorescence. By using RePCA, we identified a series of 24 potential interaction partners or substrates of the serine/threonine protein kinase AKT1. We confirm that α-actinin 4 (ACTN4) interacts physically and functionally with AKT1. siRNA-mediated ACTN4 silencing down-regulates AKT phosphorylation, blocks AKT translocation to the membrane, increases p27(Kip1) levels, and inhibits cell proliferation. Thus, ACTN4 is a critical regulator of AKT1 localization and function.